Yang Shi’s Confucian Quiet-Sitting Meditation: A Distinction from Cheng Yi and Huayan Buddhism - Song, Bin (Religions, 2024)
Yang Shi initiated the Neo-Confucian methodology of self-cultivation centered on quiet-sitting, and focusing on Yang Shi may shift the study of Confucian quiet-sitting to a more chronologically appropriate “beginning-forward” approach. Incorporating techniques such as breathing and calming the mind, Yang’s approach to self-cultivation follows a model of returning to the state of centrality through quiet-sitting, and then preserving and expanding that state in moments of everyday life. This model is based on a moral psychology and metaphysics that views the comprehensive pattern-principle of the universe, Tianli, as fully manifest in the vital state of the human heartmind achievable through the practice of quiet-sitting. This view inherits major features of Cheng Hao’s philosophy while distinguishing itself from Cheng Yi’s. Yang Shi’s reflections on the differences between Confucian and Buddhist contemplative practices also indicate, despite his view being closer to the Huayan Buddhist metaphysical perspective of perfect fusion between pattern-principle and things compared to Cheng Yi, an insistence on characterizing his quiet-sitting philosophy as distinctively Confucian.